Lexical-syntactic and syntactic stylistic devices in pessimistic utterances (A study of the 20th century English prose). - Yefremova, Nataliia V. (Комунальний заклад вищої освіти «Луцький педагогічний коледж» Волинської обласної ради, 2024)
This paper focuses on the stylistic means and devices that contribute to the generation of pessimistic discourse in the 20th-century English prose. The study aims to identify the stylistic expressive means and devices employed by the authors to create the pessimistic tonality of narration. The study employs a convenience sampling method and content analysis to ensure the reliability and validity of the results. It has been carried out by using the Tropes V8.4 software which identified both direct (the lexical units designating the phenomenon of pessimism) and indirect (the contextual markers of pessimism) indicators of the pessimistic narration. It has been revealed that pessimistic utterances are constructed by the authors of literary works applying to the stylistic context, which highlights the internal emotional state of a pessimist, i. e. their feelings, emotional and behavioral reactions. The research identifies lexical-syntactic (simile) and syntactic (rhetorical questions, inversion, repetition, parallel constructions, interrupted sentences) stylistic devices implemented in the pessimistic utterances to express the pessimistic character’s worldview revealing the range of basic, adjacent, and related qualitative features of pessimism which create general emotional tension and increase the expressiveness of narration. It has been determined that lexical-syntactic and syntactic stylistic devices in pessimistic utterances refer to pessimism in its situational aspect, that is as a product of individual experience reflecting the expectation of a negative result in a specific situation involving certain adaptive actions. The study contributes to the development of linguistic semantics, communicative linguistics, and discourse studies by enriching the knowledge of idiostyles. The proposed methodology of the given research is considered promising within the framework of linguistic semiotics and psycholinguistics.

У статті висвітлено стилістичні засоби і прийоми, які сприяють породженню песимістичного дискурсу в англомовній прозі ХХ століття. Метою дослідження є виявлення стилістичних засобів і прийомів, за допомогою яких автори художніх творів створюють песимістичну тональність оповіді. У дослідженні застосовано метод суцільної вибірки та контент-аналіз для забезпечення надійності та достовірності результатів. Контент-аналіз було здійснено за допомогою програмного забезпечення Tropes V8.4. У ході аналізу було визначено як прямі (лексичні одиниці, що позначають феномен песимізму), так і непрямі (контекстуальні маркери песимізму) індикатори песимістичного наративу. Встановлено, що песимістичні висловлення створюються авторами літературних творів на основі стилістичного контексту, який висвітлює внутрішній емоційний стан персонажа-песиміста, тобто його/її почуття, емоційні та поведінкові реакції. У ході дослідження виявлено лексико-синтаксичні (порівняння) та синтаксичні (риторичні запитання, інверсія, повтор, паралельні конструкції, перервані речення) стилістичні засоби, які автори літературних творів включають у песимістичні висловлення для відображення світосприйняття персонажа-песиміста, експлікуючи низку базових, суміжних та супутніх якісних ознак песимізму, що створює загальну емоційну напругу та посилює виразність оповіді. Визначено, що лексико-синтаксичні та синтаксичні стилістичні засоби в песимістичних висловленнях сприяють реалізації ситуативного песимізму, як продукту індивідуального досвіду, що відображає очікування негативного результату в конкретній ситуації та передбачає певні адаптивні дії. Проведене дослідження сприяє розвитку лінгвістичної семантики, комунікативної лінгвістики та дискурсології. Запропонована методологія вважається перспективною в рамках лінгвістичної семіотики та психолінгвістики.
Keywords: Песимізм; песимістичне висловлення; песимістичний дискурс; якісні ознаки песимізму; песимістична тональність; лексико-синтаксичні стилістичні засоби; синтаксичні стилістичні засоби; 811.111’367’373’38